1996
DOI: 10.1021/js9600989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Partial Hepatectomy on Theophylline Pharmacokinetics in Rats

Abstract: The influence of partial hepatectomy on the pharmacokinetics of theophylline was determined in rats. The pharmacokinetics of intravenous theophylline was studied in unhepatectomized rats (control group: CG) and in hepatectomized rats (HG) 12 h after 70% hepatectomy. Liver function was monitored in both groups by measurements of total and direct bilirubin, transaminases GOT and GPT, and plasma protein. Seventy per cent hepatectomy caused significant liver dysfunction: transaminase levels (GOT and GPT) increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Comparing to an average hepatic blood flow of 50 ml/min/kg in rats (Lin, 1990), the tea catechins can be considered to have moderate clearances. The steady state volumes of distribution (V ss ) of these catechins in rats are in the range observed for other polar drugs (Fabre et al, 1977;Maza et al, 1996;Burstein et al, 1999) and are considered to have small distribution volumes. The discrepancies observed between the animal pharmacokinetic data and human situations could be because the oral bioavailability (F) of green tea catechins is also low in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing to an average hepatic blood flow of 50 ml/min/kg in rats (Lin, 1990), the tea catechins can be considered to have moderate clearances. The steady state volumes of distribution (V ss ) of these catechins in rats are in the range observed for other polar drugs (Fabre et al, 1977;Maza et al, 1996;Burstein et al, 1999) and are considered to have small distribution volumes. The discrepancies observed between the animal pharmacokinetic data and human situations could be because the oral bioavailability (F) of green tea catechins is also low in humans.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study performed in our laboratory showed that theophylline pharmacokinetics change significantly after hepatectomy (7). However, there are few studies about the influence of hepatic regeneration post-hepatectomy on drug pharmacokinetics.…”
Section: Discussionmentioning
confidence: 94%
“…The pharmacokinetics of theophylline, a low hepatic clearance drug, has been shown to be altered after partial hepatectomy (7) in rats. In the present study we have studied the influence of hepatic regeneration after partial hepatectomy on the pharmacokinetics of theophylline also in the rat.…”
Section: Introductionmentioning
confidence: 99%